Chrome Hole Dermatitis Due to Work Habit of Electroplating Workers in Candi, Sidoarjo, Indonesia - Fasya, Abdul Hakim Zakkiy; Lusno, M. Farid Dimyati; Haksama, Setya (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
abstract